Electron Paramagnetic Resonance and petrographic analysis for dating Mesolithic and Neolithic pottery from Al Khiday (Sudan). (June 2016) - Bortolussi, Claudia; Zoleo, Alfonso; Maritan, Lara; Collauto, Alberto; Brustolon, Marina; Marrale, Maurizio; Parlato, Aldo; Usai, Donatella
Abstract: Electron Paramagnetic Resonance (EPR) dating, like luminescence techniques, is based on the time-dependent accumulation of trapped charges at mineral defect centres. However, Fe(III) ions prevent the common Continuous Wave (CW-EPR) approach for dating pottery, which always contains iron. The Pulsed method (ED-EPR) allowed this limitation to be overcome, with recording of radiation-induced defect signals, as shown by increased signal intensity after artificial irradiation of samples. The method was applied to studying Mesolithic and Neolithic pottery from Al Khiday (Central Sudan), characterized by quartz-rich tempers and coming from dated contexts. As the occurrence of a natural ED-EPR signal was found to be related to the quartz grain size of the temper, a petrographic study was carried out. This first attempt at age determination of pottery by ED-EPR meant that experimental conditions and important parameters could be taken into account in developing a new dating procedure. Highlights: Radiation-induced defects in prehistoric pottery were detected through pulsed EPR. Paleo-dose estimation in pottery through pulsed EPR was tempted. A correct trend of signal intensity vs. irradiation dose was obtained. Pulsed EPR paleo-dose was overestimated compared to SAR-TL. A relationship between quartz grain-size and signal intensity was found.